The Correlation Between Awareness of Sustainable Fashion and Willingness to Pay with Intention to Purchase Sustainable Fashion Products - Ariabryna Batari Nadyasworo; S. Rouli Manalu; Amida Yusriana (Interaksi Online, 2023)
The rapid growth of the fast fashion industry has given rise to a new phenomenon referred to as sustainable fashion, hence prompting a paradigm shift in consumers' perspectives towards their clothes consumption habits. The objective of this study is to investigate the correlation between customer awareness of sustainable fashion and their willingness to pay, specifically in relation to their intention to purchase sustainable fashion products. The hypotheses posited in this study are derived from the theoretical framework of the Theory of Reasoned Action. The data for this study was collected from a sample of 310 participants through an online survey. The sampling approach employed was non-probability sampling, specifically purposive sampling. The selection of participants for the survey was based on certain criteria, (1) Male and female from Indonesia (2) Male or female consisted of individuals between the ages of 18 and 50.This study tested one hypothesis. As a result, it shows that awareness of sustainable fashion and willingness to pay, does correlate positive and significant with intention to purchase sustainable fashion products with a result of 0.000 (<0.01) on both variables. The aforementioned evidence supports the validity of the existing theory, that customers who have a greater understanding about the problems related with the consequences of fast fashion or the opposite of sustainable fashion are more likely to make purchases of sustainable fashion products. The findings of this study provide an important implication as knowledge of the impact of various barriers to sustainable fashion consumption can increase their intention to purchase sustainable fashion goods. Although public awareness of the negative environmental effects of the fashion industry is relatively high, there is still much work to be done to educate consumers on the consequences of their decisions. Furthermore, Indonesian market has already demonstrated a willingness to pay a higher price for environmentally and socially responsible products. Thus, it may serve as an encouragement for both global and regional fashion brands to make the transition towards sustainability.